Discovery Learning-Oriented Learning Video in Social Science Integrated Studies: Water Cycle Material for Grade V - Silvia Grace Kartika Nyudak; Ni Wayan Rati; I Kadek Suartama (Jurnal Media dan Teknologi Pendidikan, 2025)
The low motivation and understanding of students towards the concept of the water cycle is abstract and difficult to visualize. The purpose of this study is to develop and analyze the feasibility, practicality, and effectiveness of learning videos oriented to the Discovery Learning model in increasing students' learning motivation. This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, three classroom teachers, and nine elementary school grade V students. The data collection technique was carried out through validation questionnaires, practicality questionnaires, and pre-test and post-test tests for effectiveness tests. Data analysis techniques include qualitative descriptive analysis to examine validation results and quantitative descriptive analysis with the Paired Sample T-Test to test effectiveness. The results of the study show that Discovery Learning-oriented learning videos have a high level of validity, excellent practicality, and significant effectiveness in increasing students' motivation to learn. The implications of this study confirm that the application of Discovery Learning-based learning videos can be an innovative alternative in IPAS learning, encourage student-centered learning, and support the strengthening of the Pancasila Student Profile through increasing curiosity, independence, and critical thinking.